Wildfires and social media discourse: exploring mental health and emotional wellbeing through Twitter - García, Yury E.; Villa-Pérez, Miryam Elizabeth; Li, Kuang; Tai, Xiao Hui; Trejo, Luis A.; Daza-Torres, Maria L.; Montesinos-López, J. Cricelio; Nuño, Miriam (Frontiers in Public Health, 2024)
The rise in global temperatures due to climate change has escalated the frequency and intensity of wildfires worldwide. Beyond their direct impact on physical health, these wildfires can significantly impact mental health. Conventional mental health studies predominantly rely on surveys, often constrained by limited sample sizes, high costs, and time constraints. As a result, there is an increasing interest in accessing social media data to study the effects of wildfires on mental health. We studied Twitter users affected by the California Tubbs Fire in 2017 to identify data signals on emotional well-being and mental health. This analysis aimed to examine tweets posted during the Tubbs Fire disaster to gain insights into how the event impacted people. We analyzed data spanning October 8 to October 31, 2017, the peak activity period. A series of analyses were conducted on the tweets to uncover word usage, sentiment, temporal patterns of word occurrence, and emerging topics related to the unfolding crisis. The findings show increased user engagement on wildfire-related Tweets, particularly during nighttime and early morning, especially at the onset of wildfire incidents. Subsequent exploration of emotional categories using Linguistic Inquiry and Word Count (LIWC) revealed a substantial presence of negative emotions at 43.0%, juxtaposed with simultaneous positivity in 23.1% of tweets. This dual emotional expression suggests a nuanced and complex landscape, unveiling concerns and community support within conversations. Stress concerns were notably expressed in 36.3% of the tweets. Lastly, discussions about mental health, worries about air quality, feelings of emotional exhaustion and support, and criticism of the president's response to the wildfire emergency emerged. Social media data, particularly Twitter data captured during wildfire seasons offers an opportunity to evaluate the immediate effects of wildfires on communities.